A Triptych Inquiry: Rethinking Sustainability, Innovation, and Financial Performance - Timo Busch; Bryan T. Stinchfield; Matthew S. Wood (Tinbergen Institute, 2011)
Management scholars have sought to answer the question: is there a financial payoff for ad-dressing ecological and social issues? We move beyond this question and include a time com-ponent for corporate financial performance (CFP) and a firm's innovativeness in order to ask: when does it pay? Combining a contingency perspective with the resource-based view of the firm clarifies the positive relationship between corporate environmental and social perform-ance (ESP) and CFP, which only holds in the long-term but not in the short-term. Further, we find support for a moderating effect of innovation on the relationship between the ESP and short-term CFP as suggested by the literature. However, we empirically show that in the long-term, innovation mediates the ESP-CFP relationship suggesting that innovation should be considered as a long-term investment required to unlock the full potential of ESP initiatives.
Keywords: G30; M14; L20; Q01; 330; Sustainable development; innovation; firm performance; Tobin's q; moderation and mediation; Innovation; Unternehmenserfolg; Tobins Q; Unternehmensfinanzierung; Nachhaltigkeit; USA